Analisis Fungsi Cerita Miyowor bagi Masyarakat Asli Etnik Wamesa di Windesi Kabupaten Teluk Wondama - Suabey, Rinetha Stella (Neolectura, 2024)
The Miyowor story, a significant part of the oral tradition of the Wamesa ethnic community in Windesi, Teluk Wondama Regency, serves multiple functions within the community. This study explores the various roles the Miyowor story plays, including its aesthetic, religious, and social functions. The aesthetic function is further divided into symbolic and didactic elements, where the story uses symbols like the sun, sago, and the location of Mayawor to convey deeper meanings. The didactic function imparts moral lessons and ethical values, encouraging responsible and honest behavior. The religious function highlights the community's beliefs in higher powers, as illustrated by the character Masarasetumi. The social function underscores the importance of cultural heritage, emphasizing the role of sago and traditional knowledge in the community's daily life. This research aims to provide a comprehensive understanding of how the Miyowor story enriches the cultural identity and social cohesion of the Wamesa people. By preserving and analyzing such oral traditions, the study contributes to the broader appreciation of indigenous knowledge and cultural continuity.